Simulation of AC-DC Buck Boost Converter Control Based on Fuzzy Logic - Faisal, Ahmad Faisal Ahmad; Tharo, Zuraidah; Septiany, Anggie (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2024)
Power quality is an important issue currently in the field of electrical equipment and electric power, so engineers do a lot of research on power quality. As technology develops, more and more electrical equipment is used, many electrical equipment use electronic power such as converters and others. Remembering previous research that has been carried out, namely, Simulation of AC-DC Buck Boost Converter Control with Proportional Integral Derivative (PID) using Matlab Simulink. For this reason, further research needs to be carried out with a different control system, namely fuzzy logic. By using fuzzy logic control, the simulation results show that fuzzy logic control is able to maintain the power factor value on the input side as well as the output voltage and output current values on the AC-DC buck boost converter. The rise time value shows a short and constant value based on each V reference. However, the overshoot value was not found, nor was the peak time, peak time was not found because there was no overshoot value in the output voltage and output current waveforms in the AC-DC buck boost converter simulation with a fuzzy logic controller using Matlab Simulink.